Socio-Economic Factors Affecting Agricultural Production and Income in Bangladesh - Susmita Das; Paritosh Mondal (Journal of Agricultural Socio-Economics (JASE), 2021)
The study assessed some factors that determine agricultural production and income in Bangladesh. The factors that were addressed in the study were land, labour, capital, ethnicity, gender etc. It aimed to analyze the socio-economic characteristics of the farmers in Bangladesh, to investigate the level of agricultural production activities and to identify the agricultural production problems in Bangladesh. The target population was the farmers of eight divisions in Bangladesh.  The data were obtained from structured questionnaires, semi-structured interviews and FGD. Multiple linear regression of model fourteen explanatory variables was used to analyze the characteristics of the factors mentioned above in context of farm production and income. The result of data analysis showed that the variables such as gender, age, years of schooling, service area, operational farm size, cow-shed, electricity, radio, mobile phone, television, computer, bicycle, motorcycle etc. affect farmers’ production and income. The research also found gender parity and small farm holding in farming. There should be provision of effective agricultural information dissemination services by using ICT tools in farming. Special emphasis should be given to eliminate gender disparity and resolve small farm holding problem to ensure farm production and income generation.